2022
DOI: 10.1101/2022.08.31.505985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroinvasion and anosmia are independent phenomena upon infection with SARS-CoV-2 and its variants

Abstract: Anosmia was identified as a hallmark of COVID-19 early in the pandemic, however, with the emergence of variants of concern, the clinical profile induced by SARS-CoV-2 infection has changed, with anosmia being less frequent. Several studies have focused on the neuropathogenesis of the original SARS-CoV-2, but little is known about the neuropathological potential of the variants. Here, we assessed the clinical, olfactory and inflammatory conditions of golden hamsters infected with the original SARS-CoV-2, its OR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 98 publications
2
10
0
Order By: Relevance
“…More recent data detected SARS-CoV-2 in the olfactory bulb for all five variants tested, though infection led to smell loss in only some variants [43]. Consistent with mouse data [33], this suggests that viral-induced anosmia may be independent of neuroinvasive capacity [43]. Indeed, hamsters frequently have lasting olfactory perturbations following SARS-CoV-2 infection, indicating that they may be useful models for post-COVID olfactory dysfunction [44,45].…”
Section: Animal Pathogenesissupporting
confidence: 69%
See 1 more Smart Citation
“…More recent data detected SARS-CoV-2 in the olfactory bulb for all five variants tested, though infection led to smell loss in only some variants [43]. Consistent with mouse data [33], this suggests that viral-induced anosmia may be independent of neuroinvasive capacity [43]. Indeed, hamsters frequently have lasting olfactory perturbations following SARS-CoV-2 infection, indicating that they may be useful models for post-COVID olfactory dysfunction [44,45].…”
Section: Animal Pathogenesissupporting
confidence: 69%
“…However, olfactory neurotropism of SARS-CoV-2 in hamsters seems to be highly dependent on the viral isolate, as some have been shown to replicate in OSNs without CNS infection [39,40], while others infect OSNs and invade the CNS [41] Some subsequent variants, such as Delta in one study [25] and D614G in another [42], cause even more OSN infection and CNS neuroinvasion, with variants such as Omicron having fewer of these tendencies [25,42]. More recent data detected SARS-CoV-2 in the olfactory bulb for all five variants tested, though infection led to smell loss in only some variants [43]. Consistent with mouse data [33], this suggests that viral-induced anosmia may be independent of neuroinvasive capacity [43].…”
Section: Animal Pathogenesismentioning
confidence: 98%
“…Hamsters inoculated with D614G showed cytokine/chemokine upregulation and microglial proliferation in the olfactory bulb [46]. However, a recent study by de Melo et al [140] suggested that the degree of olfactory dysfunction may not be directly associated with the variant's neuroinvasive capability. The authors showed that all variants were neuroinvasive in hamsters, but the rate of olfactory dysfunction differed: high in the wild-type (SARS-CoV-2 Wuhan), less in Gamma and absent in Delta and Omicron.…”
Section: Sars-cov-2 Variants and Olfactory Dysfunctionmentioning
confidence: 97%
“…ORF7 mutations were noted in SARS-CoV-2 variants [141][142][143]. When the ORF7ab sequence was replaced in the wild-type virus, the infected hamsters did not develop smell loss despite even higher viral titres in the olfactory bulb [140].…”
Section: Sars-cov-2 Variants and Olfactory Dysfunctionmentioning
confidence: 99%
“…Alternatively, the nervus terminalis may be considered another path for SARS-CoV-2-induced OD and neural damage via trans -synaptic transmission mechanism ( Gandhi et al, 2020 ). The nervus terminalis (or terminal nerve) is closely positioned next to the olfactory nerve, which are located on the anterior and ventromedial surface of the olfactory bulb ( Sonne et al, 2017 ), and this is where the evidence for the presence of SARS-CoV-2 RNA is found ( Khan et al, 2021 ; de Melo et al, 2022 ). The nervus terminalis neurons express ACE2, which allows the binding of the spike protein from SARS-CoV-2 ( Bilinska et al, 2021 ; Butowt and von Bartheld, 2022 ).…”
Section: Routes Of Viral Invasionmentioning
confidence: 99%